Periurbanisation and natural hazards - Laurent Astrade; Céline Lutoff; Rachid Nedjai; Céline Philippe; Delphine Loison; Sandrine Bottollier-Depois (Revue de Géographie Alpine)
In mountainous areas in recent decades urbanisation has expanded to areas where low ground adjoins mountainsides that are unstable in a number of respects. Periurbanisation in mountain basins with unstable sides poses specific problems that local players have to address. The Lavanchon basin (southeast of Grenoble), which is subject to very rapid urban growth combined with particularly dynamic mountainsides, is representative of the way activity is being brought into closer contact with potential hazards. A diachronic study of changes in land use between 1956 and 2001 shows how valley infrastructures at the bottom of mountainsides have become increasingly dense. In this context, a survey was carried out among a number of residents in the Lavanchon basin in an attempt to evaluate the degree of awareness that the population has of the natural hazards to which it is exposed. The results show that slightly more than half of the population surveyed was aware of the problem of natural hazards being present in the area, with most inhabitants being more concerned about industrial and pollution hazards. New residents were unaware of or were unwilling to accept the reality of hazards. The low incidence of significant natural events, the effectiveness of the protective structures built, the absence of information provided by the public authorities and the division of the basin between several management bodies appear to have engendered a feeling of safety from natural phenomena. The geographical distribution of appreciation of the hazard clearly shows a distinction between those inhabitants living on the low ground and those at the bottom of the mountainsides, and this corresponds fairly closely with the historical and current location of the main potentially hazardous events that have occurred.